Educational neuroscience - Patten , Kathryn E.; Campbell, Stephen R. (Educational philosophy and theory special issue book series., 2011)
"Educational Neuroscience provides an overview of a wide range of recent initiatives in educational neuroscience implicating and pertaining to mind, brain, and education. Contributions from top researchers in the field examine a variety of concerns, issues, and directions pertaining and relating to educational neuroscience and mind, brain, and education more generally, focusing on three main areas: motivations, aims, and prospects theories, methods, and collaborations challenges, results, and implications Chapters promote interdisciplinary perspectives and further establishment of theoretical and empirical bases for research and scholarship bridging Education and the Neurosciences. Though not exhaustive, these chapters identify various parties, agencies, organizations, and initiatives involved in facilitating and furthering development in the field, providing a compendium of on-going efforts to help establish theories, models, methods, ethics, and common language. "--